ANALISIS NILAI PENDIDIKAN KARAKTER PADA MATERI CERITA PELAJARAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR - Sisvissia Srimawirya; Syaiful Musaddat; Abdul Kadir Jaelani; Ida Bagus Kade Gunayasa (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2021)
This research as a purpose to know how the form of the education character value and how the composition of education character value contained of the story material in Indonesian Language leraning in grade IV of students book SD/MI grade IV theme 8 regions where the 2013 curriculum book revised edition 2017. Type of this research is descriptive research. Technique of collecting data used in this research is gather and note methods. The instrument used in this research is data card and guidelines for determining the education character value. Technique analysis carried out in this research include data reduction, data presentation, and data verification. Based on the result of analysis the data that have been carried out character value that appear includes: creative character value and social carriing character value with a percentage reaching 38,89 %, the honest of character value with a percentage reaching 33,33 %, hard work character value with a percentage reaching 27,78 %, religious character value and curiosity character value with a percentage reached 16,67%. If compared with character value that appear only once, that is nationalism character, homeland, respect of achievement, communicative, carring of environment and responsibility percentage 5,6%. Therefore, it could be conclude in this research founded 37 educations character values